AN EXOTIC KIND OF COSMIC MATERIAL: GRAPHITE-CONTAINING XENOLITHS FROM THE KRYMKA (LL3.1) CHONDRITE - Semenenko V.P.; Girich A.L.; Nittler L.R. (My University, 2004)
Seven graphite-containing xenoliths were found in the Krymka (LL3.1) chondrite. The xenoliths have the following chemical and mineralogical characteristics which distinguish them from the Krymka host: (1) low totals in bulk chemical analyses obtained by electron microprobe; (2) high bulk Fe abundances; (3) a uniform recrystallized, chondrule-free texture; (4) the presence of euhedral graphite and carbon-rich material; (5) higher quantities of troilite and metal; (6) a relatively homogeneous composition of silicates; (7) a distinctive composition of metal, chromite and phosphate; (8) isotopically heavy C in graphite compared to both bulk Krymka and graphite in other ordinary chondrites. The xenoliths are mineralogically similar, but not identical, to the Krymka carbonaceous clast K1, which bears graphite microcrystals, organic compounds and mysterite. They resemble carbonaceous chondrites, both chemically and isotopically. The mineralogical, chemical and isotopic data for the graphite-containing fragments suggest that this material represents metamorphosed varieties of a previously unknown type of unequilibrated carbonaceous matter. Most likely, the graphite has a metamorphic origin and was crystallized from C-containing precursor materials through the following transformation sequence: organic compounds → C-rich material → graphite.
Keywords: chondrite